Comparison between symmetrical and asymmetrical single phase multilevel inverter with diode-clamped topology - Nami, A.; zare, F.; Ledwich, G.; Ghosh, Arindam; Blaabjerg, F. (Institute of Electrical and Electronics Engineers ( IEEE ), 2008)
In this paper, a different configuration based on different DC bus voltage for a diode-clamped multilevel inverter has been presented. Two different symmetrical and asymmetrical arrangements of a four-level diode clamped inverters have been compared, in order to find an optimum arrangement with lower switching losses and optimised output voltage quality. The optimised asymmetrical arrangement has been compared with a conventional four- level inverter. The comparison results show that an asymmetrical configuration can obtain more voltage levels in output voltage with same number of component compared with the conventional four-level inverter and this will lead to the reduction of harmonic content of output voltage. A predictive current control technique has been carried out to verify the viability of new configuration. The advantages of this control method are simplicity and applicability for n-level multilevel inverters, without a significant change in the control circuit.